Democracy, Dialogue, and Community Action : Truth and Reconciliation in Greensboro - Jovanovic, Spoma, 1958- (Book collections on Project MUSE., 2012)
Spoma Jovanovic is associate professor of communication studies at the University of North Carolina at Greensboro